2020
DOI: 10.1017/wsc.2020.87
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide symptomology and the mechanism of action of methiozolin

Abstract: Methiozolin is a new herbicide for control of annual bluegrass (Poa annua L.) in several warm and cool season turfgrasses with an unknown mechanism of action (MOA). In the literature, methiozolin was proposed to be a pigment inhibitor via inhibition of tyrosine aminotransferases (TATs) or a cellulose biosynthesis inhibitor (CBI). Here, exploratory research was conducted to characterize the herbicide symptomology and MOA of methiozolin. Arabidopsis (Arabidopsis thaliana L.) and P. annua exhibited a similar leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…After several failed attempts to discover the MoA of cinmethylin, it was reported in 2018, almost 35 years after being introduced, to inhibit the synthesis of medium-chain-length fatty acids by inhibition of acyl-ACP thioesterases, a new MoA . It is interesting that another herbicidal compound (the isoxazoline methiozolin (Figure ), commercialized in the Far East) that is structurally similar to cinmethylin had also been misinterpreted with cinmethylin to be phytotoxic through the inhibition of tyrosine amino transferase and was very recently found to also act through the inhibition of acyl-ACP thioesterases . Cinmethylin was not a significantly successful herbicide when first commercialized, and its analogs were apparently even less viable as potential herbicides; however, decades after its first introduction, the rapid increases in the herbicide resistance of weeds have caused renewed interest in cinmethylin, especially after its novel MoA was clearly determined.…”
Section: Herbicidesmentioning
confidence: 99%
“…After several failed attempts to discover the MoA of cinmethylin, it was reported in 2018, almost 35 years after being introduced, to inhibit the synthesis of medium-chain-length fatty acids by inhibition of acyl-ACP thioesterases, a new MoA . It is interesting that another herbicidal compound (the isoxazoline methiozolin (Figure ), commercialized in the Far East) that is structurally similar to cinmethylin had also been misinterpreted with cinmethylin to be phytotoxic through the inhibition of tyrosine amino transferase and was very recently found to also act through the inhibition of acyl-ACP thioesterases . Cinmethylin was not a significantly successful herbicide when first commercialized, and its analogs were apparently even less viable as potential herbicides; however, decades after its first introduction, the rapid increases in the herbicide resistance of weeds have caused renewed interest in cinmethylin, especially after its novel MoA was clearly determined.…”
Section: Herbicidesmentioning
confidence: 99%
“…Besides the reported cinmethylin binding to FAT, 7,25 this array of assays demonstrates a strong FAT binding affinity in the nanomolar range and inhibition of FAT enzymatic activity by cinmethylin. Studying the metabolic changes revealed that, amongst other effects, cinmethylin treatment led to an altered galactolipid composition.…”
Section: Discussionmentioning
confidence: 78%
“…This included the rice herbicides/safener oxaziclomefone, bromobutide, dymron, and dimepiperate, the turf herbicides methyldymron and orbencarb, the rape herbicides tebutam and clomazone, as well as the Brassica napus L. and cereal herbicide bixlozone. We also included the rice and turf herbicide methiozolin as a positive control, as we recently described FAT inhibition as its predominant mode of action 25 . An overview of the structures of discussed compounds is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations